Characterization and evaluation of Indian multivoltine silkworm (Bombyx mort) germplasm - MUKHERJEE, S; MUKHERJEE, P; SAHANI, N K; SINHA, R K (The Indian Journal of Agricultural Sciences, 2013)
Variability, heritability, genetic gain as per cent of mean and correlations were studied for 9 quantitative charactersamong 56 muitivoltine silkworm (Bombyx mori L.) breeds. Wide variability was recorded among the breeds formorphological and quantitative characters. Fecundity, weight of mature larvae, fifth instar' larval duration, yield/1O 000larvae by weight, cocoon weight and shell weight showed high genotypic coefficient of variation (gcv), heritability andgenetic advance as per cent of mean, indicating possibility of further improvement through selection. The correlation ofyield/1O 000 larvae by weight with cocoon weight, shell weight and shell ratio (%) was significant and positive, whereasyield/1O 000 larvae by number did not show association with any of the characters except yield/10 000 larvae by weight.Similarly, total larval dumtion was positively correlated with fifth instar larval duration, but both these variables werenot associated with any other characters. The study revealed that one set of variables may control the expression ofother set of characters. The breeds like 'MHMP (Y)', 'A 13', 'Hosa Mysore', 'AP 12' and 'MW 13' could be identifiedpotential genotypes for the improvement of multivoltine silkworm through appropriate breeding programme.